2005
DOI: 10.1111/j.1472-765x.2005.01780.x
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity of Campylobacter jejuni and Campylobacter coli strains isolated from healthy cattle

Abstract: Aims: To identify campylobacters isolated from clinically healthy cattle at species level by a multiplex polymerase chain reaction (m-PCR). The heterogeneity among Campylobacter jejuni and Campylobacter coli isolates was also investigated by using a restriction fragment length polymorphism (RFLP) analysis of flagellin (flaA) gene. Methods and Results: Samples of intestinal contents, gall bladders, liver and faeces were collected from a total number of 1154 healthy cattle. The samples were inoculated onto Prest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This has been seen in other studies with other typing methods as well (2,6,48) and also in regard to C. jejuni isolates from chickens, sheep, turkeys, water, and human cases (9,13,38). A wide variation of SmaI subtypes could be observed among the isolates representing the most common serotype, Pen2.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…This has been seen in other studies with other typing methods as well (2,6,48) and also in regard to C. jejuni isolates from chickens, sheep, turkeys, water, and human cases (9,13,38). A wide variation of SmaI subtypes could be observed among the isolates representing the most common serotype, Pen2.…”
Section: Discussionsupporting
confidence: 48%
“…in Finnish cattle at slaughter varied monthly between 18.8% and 44.1% during this 1-year study. In several studies performed in other countries prevalences of between 7% and 100% at slaughter have been reported (2,5,14,37,42,49). Due to the different study designs regarding various sampling methods and materials, detection methods, etc., the results are not always comparable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, predominant flaA-typing patterns of C. jejuni strains were significantly (P < 0.05) different from C. coli isolates. Acik and Cetinkaya ( 21 ) showed that among 209 isolates, 28 different flaA types were found. Twenty-three flaA types were identified among 179 C. jejuni isolates and the remaining five from C. coli isolates.…”
Section: Discussionmentioning
confidence: 99%
“…6% (4/14 beef liver) by PCR. That was higher than reported in Brazil; 1.51% (2/132 chilled beef liver)(Takeuchi et al, 2022), and Turkey; 0%(0/325 Liver samples from apparently healthy cattle by PCR)(Açik and Çetinkaya, 2005).From the other hand, our isolation rate was lower than the previous studies conducted in Washington, D.C.;15%(6/40 fresh beef liver)(Stern et al, 1984), Ottawa, Ontario; 12%(12/100)(Garcia et al, 1985), ) 33.3% then, liver (4 /14) 28.6%, and meat muscles (7/25) 28% (Table,1 and Fig.1). The fluctuation in Campylobacter species isolation rate in various studies have be attributed to many reasons as, type of examined samples, location, climate factors, hygienic measures and isolation as well as identification techniques(Jorgensen et al, 2011and Chatur et al, 2014.…”
mentioning
confidence: 55%